Vehicle Speed Meters Validation and Verification System - Kaskonas, P.; Meskuotiene, A. (Elektronika ir Elektrotechnika, 2012)
Speed meters verification principles and problems are observed in the article. Method of vehicle average speed measurement over the specified length road segment was proposed, using four laser units. The method allows to avoid synchronization between measurements of speed meter under metrological test and reference system during verification procedure and therefore to avoid vehicle speed variation influence. Developed reference speed measurement system has expanded uncertainty less than ±0.3 km/h, including vehicle speed variation term. Ill. 3, bibl. 8 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.119.3.1372